PELATIHAN PENGGUNAAN PLATFORM E-COMMERCE GUNA MENARIK MINAT SISWA BERWIRAUSAHA (PELATIHAN BAGI SISWA KELAS 3 MA ASWAJ AMBUNTEN) - Mohammad Rofik; Arief Hidayatullah Khamainy (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2021)
This training is carried out to provide provisions for students who are in grade 3 MA Aswaj, because they will soon take off their uniforms to take on the next life. Currently the problem faced by students is technological stuttering, there is even a possibility that some of them still cannot turn off the computer, besides that students are millennials who are very close to the Internet but their smartphone usage is not used as a smart phone that should be, their cellphones are only used for non-productive activities such as chatting and playing games, so it becomes necessary to provide them with an understanding of how they should use their cellphones with productive things such as selling online using e-commerce platforms such as Shope, Tokopedia, Whatsapp and Instagram. This training is important considering that they will soon take off their uniforms and will move on to the next stage, namely the world of work, one of them. The training was carried out at the MA Aswaj School located in Ambunten Timur Village, Ambunten District, in the process of implementing the training the participants were very enthusiastic about participating and providing feedback in the form of questions to the presenters. After the material was delivered, the presenters carried out a simulation of selling online using the Shope, Bukalapak, Whatsapp and Instagram applications.